PENGARUH PESAN IKLAN TELEVISI GOOGLE VERSI “CARI LIRIK” TERHADAP PENGGUNAAN FITUR OK GOOGLE PADA MAHASISWA DI BANDUNG - Aviesni Sabrina; Berlian Primadani Satria Putri (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2018)
Advertising media is one of the ways to introduce a new product to consumer. One of the advertisement types which has many advantages is television. Google is one company which use television as their advertising media. Researcher chose the